Enhanced activities of organically bound tritium in biota samples - Svetlik, I; Fejgl, M; Malátová, I; Tomaskova, L (Applied radiation and isotopes, 2014)
A pilot study aimed on possible occurrence of elevated activity of non-exchangable organically bound tritium (NE-OBT) in biota was performed. The first results showed a significant surplus of NE-OBT activity in biota of the valley of Mohelno reservoir and Jihlava river. The liquid releases of HTO from the nuclear power plant Dukovany is the source of tritium in this area. This area can be a source of various types of natural samples for future studies of tritium pathways.
Keywords: rostliny; radioaktivní látky znečišťující vodu; jaderné elektrárny; radioaktivní znečišťující látky; Česká republika; společenstvo; řeky; Czech Republic; Tritium; Rivers; tritium; Plants; NPPs; Nuclear Power Plants; Radiation Monitoring; monitorování radiace; Combustion; HTO; Humans; scintilace - počítání; Scintillation Counting; pilotní projekty; Pilot Projects; Biota; Radioactive Pollutants; NE-OBT; Water Pollutants, Radioactive; lidé